Accumulation of heavy metals and polycyclic aromatic hydrocarbons in soils around the industrial area of Aba, Nigeria - Ifeoma Rose Franklin; Oluchi Rose Colette Nlemolisa; Sordum Catherine Baridakara; Chukwuemeka Fortunatus Nnadozie (EQA, 2023)
The simultaneous accumulations of heavy metals and polycyclic hydrocarbons (PAHs) have gained considerable attention since soils contaminated with PAHs were frequently reported to contain high amounts of heavy metal. The present study was carried out to assess heavy metals and polycyclic aromatic hydrocarbons in soils around the industrial area of Aba. Samples were collected from Ogbor hill and Umuobo village. Umuobo village, served as the control. Heavy metals analyzed were lead, cadmium, iron, argon, manganese, mercury, zinc and copper using atomic absorption spectrophotometer method. Polycyclic aromatic hydrocarbon analyzed were naphthalene, acenaphthylene, acenaphthene,fluorine, phenanthrene, benzo (b) fluoranthene, benzo (k) fluoranthene, benzo (e) pryene, dibeno (a,h) anthracene, Indeno (1,2,3-cd) pyrene, benzo (b) triphenylene and benxo (ghi) perylene using Gas Chromatography-Flame Ionization Detection (GC-FID) method. The statistical methods used were standard error of mean, two way analysis of variance and multiple unpaired T-test of variance. Iron recorded the highest concentration in all the sampling points with the mid slope having the highest concentration of 295.83±1.15 mg/kg, while cadmium has the lowest concentration in all the points, with the valley bottom having the lowest with 0.01±0.02 mg/kg. The control recorded a very low concentration of the heavy metals in both sampling sites. The highest was at the crest with the concentration of 0.7±0.00 mg/kg (15-30 cm) in Iron. Mercury and argon were not detected in crest, mid slope and valley bottom of Ogbor hill. For the polycyclic aromatic hydrocarbon, indeno (1, 2, 3-cd) pyrene recorded the highest concentration at both the crest and mid slope, with 2.53±0.43 ppm and 1.02±0.03 ppm respectively, while Benzo (e) pryene recorded the highest concentration at the valley bottom with 0.68±0.28 ppm. The control also recorded the lowest concentrations of the entire polycyclic aromatic hydrocarbon. The highest concentration was recorded at the crest with 1.86±1.64 ppm (15-30 cm) of Indeno (1, 2, 3-cd)pyrene. It is recommended that the industry owners/operators should ensure that effluent treatment plants are installed in their facilities, and should be operated at optimum conditions and manned by qualified personnel.